STRATEGI KOMUNIKASI GURU SEKOLAH MENENGAH KEJURUAN DALAM MENERAPKAN PEMBELAJARAN DARING (STUDI KASUS DI SMK NEGERI 3 KOTA BEKASI) - Mulyana, Fajar Rizki (Universitas Negeri Surabaya, 2022)
The Covid-19 pandemic in Indonesia has had an impact on various sectors. In the education sector, the government decided to shift online learning from elementary to tertiary levels. With this policy, teachers must develop communication strategies so that online learning can run effectively. The purpose of this study was to determine the communication strategies used by teachers of SMKN 3 Bekasi City in online learning. This research uses a qualitative approach with a case study method. Data collection was done through direct interviews and observation. Interviews were conducted with teachers of productive subjects in each study program, and observations were made in online classes held by each department. The results of this study indicate that the communication strategies used by SMKN 3 Bekasi City teachers in the application of online learning are as follows: (1) Using the lecture method to convey messages in online classes held in educational applications, such as zoom and google meet. (2) Using video and PPT media to assist the learning process. (3) Discuss with students before and after class as a form of interaction. (4) Carry out tests or quizzes as learning assessments through electronic communication channels, such as google forms and quiziz.